Characterization of Toluene- and Quinoline-Insoluble Extracted from Pyrolysis Fuel Oil-Derived Pitch for Manufacture of C/C Composites - Kim, Hong Gun; Kim, Yong-Sun; Kwac, Lee Ku; Kuk, Yun-Su; Shin, Hye Kyoung (International journal of precision engineering and manufacturing, 2018)
We herein report extraction and characterization of toluene-insoluble (TI) and quinoline-insoluble (QI) from pyrolyzed fuel oil (PFO) derived-pitch. The X-ray diffraction patterns demonstrated that QI component exhibited a more crystalline character than TI component. In addition, analysis by Fourier transform infrared spectroscopy (FT-IR) indicated the presence of signals at 3060 cm -1 for both TI components and QI components, which corresponded to the stretching of aromatic C-H bonds. As the intensity of this signal was greater than that of the peak at 2943 cm -1 corresponding to the stretching of aliphatic C-H bonds, it was clear that these components contained higher quantities of aromatic components than the original pitch sample. Furthermore, thermogravimetric analysis (TGA) indicated that the TI and QI components improved thermal stabilities and residues compared to the pitch sample (i.e., TI 75 wt% and QI 65 wt% at 850 oC). Finally, scanning electron microscopy (SEM) images confirmed that TI components were surrounded by β-resin (quinoline solubles in TI components) between the QI regions, which were themselves composed of aggregated grain-like spheres.